A Case of Gastric Inverted Hyperplastic Polyp Found with Gastritis Cystica Profunda and Early Gastric Cancer - Lee, Sang Jin (The Korean Society of Gastrointestinal Endoscopy, 2013)
A gastric inverted hyperplastic polyp is a rare type of gastric polyp and is characterized by downward growth of a variety of mucosal components into the submucosa. The polyp consists of columnar cells resembling foveolar epithelium and pyloric gland epithelium and can coexist with gastritis cystica profunda. Frequently, adenocarcinoma can coexist, but the relation is not clear. A 77-year-old male underwent endoscopic submucosal dissection due to early gastric cancer. A gastric inverted hyperplastic polyp was found in the removed specimen and gastric cystica profunda was also found. We report a case of gastric inverted hyperplastic polyp coexisting with gastric cystica profunda and gastric adenocarcinoma.